Effect of nanoporous membranes thickness in electrochemical biosensing performance: application for the detection of a wound infection biomarker - Toyos-Rodríguez, C.; Valero-Calvo, D.; Iglesias-Mayor, A.; de la Escosura-Muñiz, A. (Frontiers in Bioengineering and Biotechnology, 2024)
Formed by the voltage mediated anodization of Al at an acidic pH, nanoporous alumina membranes present a honeycomb-like structure characterized by two main parameters involved in their performance in electrochemical immunosening: pore diameter and pore thickness. Although this first one has been deeply studied, the effect of pore thickness in electrochemical-based nanopore immunosensors has been less taken into consideration. In this work, the influence of the thickness of nanoporous membranes in the steric blockage induced by the formation of an immunocomplex in their inner walls is studied for the first time. Nanoporous alumina membranes with a fixed pore diameter (60 nm) and variable pore thicknesses (40, 60, 100 um) have been constructed and evaluated as immunosensing platform for protein detection. Our results show that membranes with a thickness of 40 um provide a higher sensitivity and lower limit of detection (LOD) compared to thicker membranes. This performance is even improved when compared to commercial membranes (with 20 nm pore diameter and 60 um pore thickness), when applied for human IgG as model analyte. Such findings evidence the key relevance of the nanochannel thickness in the biosensing performance. Finally, the optimal nanoporous membranes were applied to the detection of catalase, an enzyme related with chronic wound infection and healing. A label-free immunosensor using a monoclonal antibody against anti-catalase was constructed, allowing the detection of catalase in the range of 50-500 ng/mL and with a LOD of 1.5 ng/mL. The viability of the constructed sensor in real samples was also tested by spiking artificial wound infection solutions, providing recovery values of 110 and 118%. The results obtained in this work will illuminate nanoporous membrane biosensing research, considering thickness as a relevant parameter in electrochemical-based nanoporous membrane sensors.